2000
DOI: 10.1152/jappl.2000.89.5.1884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phrenicotomy and exercise on hypoxia-induced changes in phrenic motor output

Abstract: To investigate models of plasticity in respiratory motor output, we determined the effects of chronic unilateral phrenicotomy and/or exercise on time-dependent responses to episodic hypoxia in the contralateral phrenic nerve. Anesthetized (urethane), ventilated, and vagotomized rats were presented with three, 5-min episodes of isocapnic hypoxia (11% O(2)), separated by 5 min of hyperoxia (50% O(2)). Integrated phrenic (and hypoglossal) nerve discharge were recorded before and during each hypoxic episode, for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, stimulation of these fibers alters c-Fos expression in neurons located in regions of the brainstem associated with respiratory pattern generation (Malakhova and Davenport, 2001). In addition, acute phrenicotomy alters the respiratory rate response to hypoxia in anesthetized rats (Bach and Mitchell, 2000). Interestingly, ipsilateral phrenicotomy increased baseline burst frequency in C 2 injured rats, suggesting that an inhibitory element had been removed.…”
Section: Altered Supraspinal Control Of Breathingmentioning
confidence: 95%
“…However, stimulation of these fibers alters c-Fos expression in neurons located in regions of the brainstem associated with respiratory pattern generation (Malakhova and Davenport, 2001). In addition, acute phrenicotomy alters the respiratory rate response to hypoxia in anesthetized rats (Bach and Mitchell, 2000). Interestingly, ipsilateral phrenicotomy increased baseline burst frequency in C 2 injured rats, suggesting that an inhibitory element had been removed.…”
Section: Altered Supraspinal Control Of Breathingmentioning
confidence: 95%
“…Yes/No indicates that LTF was present in some control groups, but not others within the same study. Mahamed and Mitchell, 2008 Anesth Yes Yes >60 min Julien et al, 2008 Unanesth No Yes >60 min Hsieh et al, 2008 Anesth Not reported Yes >60 min Macfarlane and Mitchell, 2007b Anesth Ling et al, 2001 Anesth Not reported Yes >60 min Anesth No Yes >60 min Zabka et al, 2001a Anesth Yes Yes >60 min Anesth No Yes >60 min Baker and Mitchell, 2000 Anesth Yes Yes >60 min Bach and Mitchell, 2000 Anesth Yes Yes >60 min Janssen and Fregosi, 2000 Anesth No No Kinkead and Mitchell, 1999 Anesth No Yes >60 min Kinkead et al, 1998 Anesth No Yes >60 min Bach and Mitchell, 1996 Anesth Yes Yes >60 min Hayashi et al, 1993 Anesth No Yes >60 min…”
mentioning
confidence: 99%
“…Originally, significant phrenic and hypoglossal (XII) LTF was consistently observed (1). In subsequent studies, phrenic LTF appeared somewhat smaller and XII LTF was not detectable (3,17). The only apparent difference between these studies is that SD rats were initially obtained from Sasco (S) and subsequently from Harlan (H).…”
mentioning
confidence: 99%